Implementation of Vigener’s Cryptographic Principles in the Dari Alphabet - Sarhang, Manizha; Spasely, Zarghoona (Journal of Natural Sciences – Kabul University, 2024)
The Vigenère cipher is a polyalphabetic encryption method that follows specific patterns and can be adapted for the Dari alphabet. Due to its simplicity and effectiveness in text encryption, it has gained significant attention. This study applies the Vigenère cipher to Dari text by utilizing a modified Vigenère square table for encryption and decryption. Encrypted sentences are systematically converted back to their original form using a text-based key, with the process demonstrated through structured tables. The primary objective of this analytical and comparative research is to assess the feasibility and effectiveness of applying this method to Dari text encryption. Given its unique characteristics, the Vigenère cipher serves as a viable approach for enhancing information security. The findings indicate that implementing this method can significantly improve the security of files, online communications, and electronic authentication.